Confirmatory Factor Analysis: User Behavior M-Commerce Gamification Service in Indonesia - Rakhmanita, Ani; Hurriyati, Ratih; Gaffar, Vanessa; Adi wibowo, Lili (JOIV : International Journal on Informatics Visualization, 2022)
Gamification of marketing is a fast-growing phenomenon and an innovation for mobile marketing. Gamification is a strategy for increasing the attractiveness of mobile consumers to encourage increased shopping behavior, loyalty, engagement, and product advocacy. Understanding the factors behind the use of gamification services in m-commerce is very interesting, and no one has done any research. This study investigates the theory of self-determination (competence, autonomy, and relatedness) and extrinsic motivation as a predictor of the use of m-commerce gamification services. Data was collected from 400 respondents who had experienced using gamification services on m-commerce. The data was then included in the analysis. Analysis of the data using confirmatory factor analysis to determine the dominant factors of gamification service users. The benefits of factor analysis confirm the dominant factors that motivate users of gamification services in m-commerce. Researchers use AMOS 18 for Windows software to assist in the data processing. The results show that extrinsic motivation is the dominant factor that motivates users of gamification services. This finding provides insight for m-commerce companies and game designers to improve gamification mechanisms based on virtual points to motivate users to be more active and continue using gamification services. For the next research, it is possible to validate the construct by using other theoretical approaches, such as adding flow theory to measure the motivational factors of gamification service users. The research object can use other applications, such as gamification services in health, education, and banking applications.